2014
DOI: 10.1590/0001-3765201420130333
|View full text |Cite
|
Sign up to set email alerts
|

Abeta(1-42) induces abnormal alternative splicing of tau exons 2/3 in NGF-induced PC12 cells

Abstract: Protein tau plays a pivotal role in the pathophysiology of Alzheimer's disease, where its hyperphosphorylation promotes aggregation and microtubule destabilization. Tau undergoes alternative splicing which generates six isoforms in the human brain, due to inclusion/exclusion of exons 2, 3 and 10. Dysregulation of the splicing process of tau exon 10 is sufficient to cause tauopathy and has shown to be influenced by beta-amyloid peptides, but splicing of other exons is less studied. We studied the effects of bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We observed that processes in these cells begin to retract. In spite the mechanism is still unknown, the effect produced in these cells indicate that immature Tau forms cease to stabilize microtubules in these cells processes [26] (Figure 4). The inclusion of exons 2 and 3 promotes the shift from immature Tau forms to their mature counterparts, stabilizing microtubules.…”
Section: The Tau Gene and Its Alternative Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that processes in these cells begin to retract. In spite the mechanism is still unknown, the effect produced in these cells indicate that immature Tau forms cease to stabilize microtubules in these cells processes [26] (Figure 4). The inclusion of exons 2 and 3 promotes the shift from immature Tau forms to their mature counterparts, stabilizing microtubules.…”
Section: The Tau Gene and Its Alternative Splicingmentioning
confidence: 99%
“…Aβ exposure promotes exclusion of exons 2/3 in undifferentiated and differentiated cells, and exclusion of exon 6 in undifferentiated cells. Scheme taken from[26].…”
mentioning
confidence: 99%
“…Therefore, abnormal variations of splicing may induce the development of multiple diseases, including cancer. Recently, Pan et al and other groups revealed that the abnormal splicing of mRNA caused such diseases as inflammatory bowel disease, Alzheimer's disease, atherosclerosis disease [11][12][13][14][15]. Data from Lawes et al and other teams discovered that some tumours, e.g.…”
Section: Introductionmentioning
confidence: 99%